Study of Umbilical Blood Lead Level and Its Relation with Pregnancy Outcome - El Khaleegy, Hany Abdul Hady; Abo baraka, Waleed Ezzat; El-moghazy, Mohammed Khairy (Journal of medical and pharmaceutical sciences, 2019)
Background: Lead exposure continues to be a major health problem that needs more attention in different health disciplines. Objective: to explore the correlation between maternal exposure and cord blood lead levels and to identify potential predictors for umbilical cord blood lead levels and its effect on pregnancy outcome. Methodology: This study is a cross sectional study, which included 100 newborns of healthy pregnant women with singleton pregnancy. The study took place from November 2017 to April 2018. All mothers complete a questionnaire about their demographic data, obstetric history. In addition, their pregnancy outcome was documented and an umbilical cord sample was drawn for determination of lead levels. Patients were divided into two groups according to umbilical cord blood lead levels (high group ≥10 µg/dl) and low group (<10 µg/dl). Results: High umbilical cord blood lead levels were associated with living or working near highly trafficked streets or roads, living or working near painting workshops, living near waste burning, working near buildings being demolished, regularly using heavy traffic streets or roads, and drinking tea, coffee or green tea, while low lead concentration was associated with taking iron and calcium supplementation. Mothers in high group had significantly lower hemoglobin, and there was a significant decrease of birth weight, length and head circumference in such group. Umbilical blood lead level (UBLL) correlates negatively with mother’s hemoglobin, neonatal birth weight, head circumference and length. Conclusion: higher umbilical cord blood lead concentrations were associated with adverse maternal and neonatal outcome. Exposure usually occupational or environmental.